Prevention for Chemotherapy-induce Phlebitis with tropical extract Oil - Vorakitticharoon, Vitkawin; Raitang, Suphanuch (Vajira Nursing Journal, 2024)
Chemotherapy-induced phlebitis (CIP) is a significant complication for cancer patients. CIP can develop as an acute phase within 24 hours after chemotherapy and is commonly observed during the second dose. The incidence of CIP is high not only in Thailand but also in other countries. In Thailand, CIP is often detected in cancer patients between the 3rd and 4th days of the chemotherapy cycle. CIP can affect patients physically, mentally, and socioeconomically. This article serves as a resource for nurses in preventing chemotherapy-induced phlebitis, exploring the potential use of various essential oils, including sesame oil, Nigella sativa extract oil, and chamomile oil, for topical application on the skin overlying the veins used for drug administration. It represents the application of evidence-based knowledge aimed at enhancing cancer patient care and reducing the incidence of chemotherapy-induced phlebitis.